(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Astarini IA, Ningsih EY, Simanungkalit D, Ardiana SA, Al Malik MD, Yusmalinda NLA, Sembiring A, Pertiwi NPD, Cahyani NKD, Collins A. 2021. Genetic variation of longtail tuna Thunnus tonggol landed in four fish markets in Indonesia based on mitochondrial DNA. Biodiversitas 22: 1644-1651. Longtail tuna (Thunnus tonggol, Family: Scombridae) is an economically valuable neritic species found in tropical and subtropical waters in the Indo-Pacific region. High catch numbers, which have been decreasing, could negatively impact this tuna’s population level. Little research has been conducted on the longtail tuna population in Indonesia. This study aims to determine the genetic diversity and potential population structure of longtail tuna landed in four fish markets in Indonesia (representing three sampling locations because two markets are relatively close to each other) based on sequences of a region of mitochondrial control region (d-loop). A total of 101 samples, out of 110, were identified and confirmed as T. tonggol species by amplifying and sequencing a fragment of d-loop (amplicons ranging from 482 - 523 bp). Neighbor-joining analysis resulted in a topology with all samples grouped into one clade with an average genetic distance of 0.020. Meanwhile, haplotype diversity (Hd) and nucleotide diversity (?) values of the longtail tuna samples were 0.9939 and 0.0192, respectively. The fixation index (Fst) value was -0.00507, with p> 0.05, which indicates that there is no significant population structure among the longtail tuna collected from four fish markets representing three sampling locations. The results of this analysis can be used as basic data in planning sustainable fisheries management efforts.